Guillaume Bottazzi painting on the Miyanomori International Museum of Art - Guillaumb (Wikimedia Commons, 2013)
Notice iconographique issue de Wikimedia Commons. Titre: Guillaume Bottazzi painting on the Miyanomori International Museum of Art. 900m² painting by Guillaume Bottazzi
Licence Creative Commons Attribution 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons